Implementing Online Learning Strategies to Strengthen Motivation and Independence Among Students in the Digital Era - Surya Eka Priyatna; Ilham Ilham; Risqiatul Hasanah (SYAMIL: Journal of Islamic Education, 2024)
Online learning has become an essential paradigm in the digital era, particularly in responding to the shifting educational landscape. However, challenges related to student motivation and independence persist, often impacting learning outcomes and engagement. This research aims to explore the implementation of strategic online learning methods to enhance motivation and independence among students, particularly in higher education settings. Using a mixed-method approach, this study combines qualitative interviews with quantitative surveys to analyze the factors influencing student engagement. Data were collected from undergraduate students at UIN Antasari, focusing on their experiences and perceptions of online learning strategies during the pandemic. The findings reveal that well-structured online learning strategies, including the integration of flexible scheduling, interactive tools, and self-directed learning modules, significantly enhance students' motivation and independence. This study contributes to the existing body of knowledge by highlighting the potential of online learning strategies to bridge gaps in traditional education, fostering not only academic success but also personal growth. The insights gained are expected to inform educators, policymakers, and institutions in designing more effective and inclusive online learning environments, particularly within the framework of Islamic education.